Youth-adult relationships and Positive Youth Development. - Johnson, Sara K. ; Bowers, E. P.; Warren, D. J. A.; Tirrell, J. M.; Lerner, J. V. (Tufts University. Tisch Library., 2016)
In this chapter, we identify developmental relationships as the ultimate goal of youth–adult interactions, and we describe the characteristics that define these types of relationships. Next, we review research on young people’s relationships with parents, natural mentors, and formal mentors, as well as how these relationships are associated with adolescent thriving. In particular, we highlight research from the 4-H Study of PYD, a longitudinal study of adolescents’ strengths, resources, and thriving from fifth through twelfth grade. Then, we describe several exemplary programs in which youth–adult relationships are capitalized on as a way to promote adolescents’ positive development. Finally, we provide recommendations based on this evidence for practitioners and policy makers, and we identify priorities for future efforts with parents and mentors.